Making Sense of Taste : Food and Philosophy - Korsmeyer, Carolyn (Book collections on Project MUSE., 1999)
"Taste, perhaps the most intimate of the five senses, has traditionally been considered beneath the concern of philosophy, too bound to the body, too personal and idiosyncratic. Yet, in addition to providing physical pleasure, eating and drinking bear symbolic and aesthetic value in human experience, and they continually inspire writers and artists. Carolyn Korsmeyer explains how taste came to occupy so low a place in the hierarchy of senses and why it is deserving of greater philosophical respect and attention."--Jacket